An overview of interventional radiology techniques for the diagnosis and management of vascular anomalies: Part 1. Issue 2 (9th January 2023) - Scollan, Margaret E.; Azimov, Neyra; Garzon, Maria C.; Tulin‐Silver, Sheryl
Abstract: Minimally invasive percutaneous and endovascular strategies performed by interventional radiologists have become the mainstays of treatment for vascular anomalies, with improved outcomes, decreased complication rates, and reduced morbidity. The aim of this article is to introduce physicians who care for patients with vascular anomalies to state‐of‐the‐art advancements in interventional radiology (IR) for diagnosis and treatment. Part 1 of this review will focus on sclerotherapy and cryoablation. Part 2 will discuss embolization, endovenous laser ablation, and image‐guided percutaneous biopsy. Select vascular anomalies will be discussed as examples to highlight IR diagnostic and/or treatment techniques.